1983
DOI: 10.1093/bja/55.6.487
|View full text |Cite
|
Sign up to set email alerts
|

An Evaluation of Rebreathing With the Bain System During Anaesthesia With Spontaneous Ventilation

Abstract: Data from 12 anaesthetized patients breathing spontaneously from the Bain system were used to calculate the degree of rebreathing occurring when the fresh gas flowrate (VF) was equal to 2, 1 and 0.7 times the estimated normal minute ventilation (Vtot). Measurements of the expired minute volume (VE) and end-tidal carbon dioxide tension (PE'CO2) were made to determine the effects of this rebreathing. No rebreathing occurred when VF was equal to twice Vtot. When VF was equal to Vtot rebreathing was usually small … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

1986
1986
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(9 citation statements)
references
References 18 publications
1
8
0
Order By: Relevance
“…The dill'crence from the low coirccntration of a decelerating flow, as in our VOI, curve, then becomes more pronounced. 'I'his influence of the flow at the end of active expiration was confirmed in experiment C. T h t x results are consistent with the discussion h y Meakin & Coates (18).…”
Section: R : I S C U Ss I O Nsupporting
confidence: 86%
“…The dill'crence from the low coirccntration of a decelerating flow, as in our VOI, curve, then becomes more pronounced. 'I'his influence of the flow at the end of active expiration was confirmed in experiment C. T h t x results are consistent with the discussion h y Meakin & Coates (18).…”
Section: R : I S C U Ss I O Nsupporting
confidence: 86%
“…Not surprisingly, such analyses unite in finding the Mapleson D system inefficient and are supported by a wealth of data from physical lung models, also employing respiratory patterns without significant expiratory pauses [12][13][14]. In studies in which there has been a n expiratory pause, its effect is indeed to reduce rebreathing in this system [ 15, 161. The value VnD used in this paper is identical to the 'area c' calculated by Meakin and Coates [7]. Their analysis demonstrated that this would be reduced if the expiratory flow decreased throughout expiration but they did not consider the expiratory pause.…”
Section: Discussionmentioning
confidence: 69%
“…They are also characteristic of lung models based on a rotating shaft linked to a piston [6]. Waveforms approximating to the exponentially declining waveform are also seen both in awake volunteers [7] and in anaesthetised patients [5,8]. This paper extends the previous work to these waveforms.…”
Section: Discussionmentioning
confidence: 55%
“…A weakness in this work was that the equations were solved only for linear flow waveforms, whereas the flow waveforms found in real patients (and those produced by many lung models) are nonlinear. Sinusoidal flow waveforms are commonly seen, especially when the respiratory rate is high [4,5]. They are also characteristic of lung models based on a rotating shaft linked to a piston [6].…”
Section: Discussionmentioning
confidence: 99%